Missing Guidewire in a Bulla: A Case Report - Hee Chul Yang; Sarah Nisivaco; Chitaru Kurihara (Journal of Chest Surgery)
The incidence of a missing guidewire during the Seldinger technique is low but can occur due to procedural errors. Reported rates vary, ranging from 0.1% to 0.8% in central venous catheterization and other vascular access procedures. We present a rare case of a retained guidewire within a pulmonary bulla following Seldinger-based chest tube insertion in a patient with ventilator-induced pneumothorax. Due to a prolonged air leak, the guidewire was removed, and wedge resection of the affected lung parenchyma, along with talc pleurodesis, was performed via video-assisted thoracoscopy. Closed thoracostomy using the Seldinger technique requires caution in emphysematous patients receiving mechanical ventilation. To facilitate lung deflation and minimize the risk of lung injury during needle and guidewire placement, the endotracheal tube can be temporarily disconnected from the ventilator. Over-insertion of the wire and dilator should be avoided. Supervision and simulation training are crucial to prevent this type of “never event.”